The Impact of Foreign Direct Investment on Economic Development in Libya during the Period (2000–2015) (Journal of human and social sciences, 2019)
This study aims to analyze the effects of foreign direct investment (FDI) on certain aspects of economic development in the Libyan economy during the period (2000–2015), using the descriptive-analytical method. The results revealed that fluctuations in the share of FDI in Libya’s GDP at varying levels indicated that the impact of FDI on economic development in Libya was only marginal. The study also showed that FDI did not contribute to the growth of economic sectors, which resulted in weak economic growth and bottlenecks between productive sectors.
Keywords: Foreign Direct Investment (FDI); Economic Development; GDP (Gross Domestic Product); Libya; Oil Sector